Zeitschrift für Wirtschaftspolitik (De Gruyter Oldenbourg, 1981)
Journal for Economic Policy is published on behalf of the Institute for Economic Policy at the University of Cologne. The Journal is open to publications from all areas of economics. Articles regarding current questions of German, European or international economic policy are preferred. At the center of each issue is the economic policy forum. It deals with topics, which are controversially discussed among the general public.